The aqueous root extract of Withania somnifera ameliorates LPS-induced inflammatory changes in the in vitro cell-based and mice models of inflammation - Sharma, Phulwanti Kumari; Kumar, Lokesh; Goswami, Yamini; Pujani, Mukta; Dikshit, Madhu; Tandon, Ruchi (Frontiers in Pharmacology, 2023)
Most critically ill COVID-19 patients have bronchitis, pneumonia, and acute respiratory distress syndrome (ARDS) due to excessive inflammatory conditions. Corticosteroids have largely been prescribed for the management of inflammation in these patients. However, long-term use of corticosteroids in patients with comorbidities such as metabolic, cardiovascular, and other inflammatory disorders is ideally not recommended due to safety issues. A potential and safer anti-inflammatory therapy is therefore the need of the hour. Withania somnifera (WS), a well-known herbal medicine used during the pandemic in India to prevent SARS-CoV2 infection, also possesses anti-inflammatory properties. In the present study, we, therefore, evaluated the effect of the aqueous extract of the roots of WS in the cell-based assays and in the experimental animal models of LPS-induced inflammation. In the NCI-H460, A549 cells and human peripheral blood mononuclear cells (PBMCs) pre-treatment with WS reduced the LPS-induced expression of the pro-inflammatory cytokines. In addition, WS extract also showed potent anti-inflammatory activity in the lung tissues of BALB/c mice challenged intranasally with LPS. We observed a marked reduction in the neutrophil counts in the bronchoalveolar lavage (BAL) fluid and inflammatory cytokines in the mice lungs pre-treated with WS. Results obtained thus suggest the potential utility of WS extract in reducing airway inflammation and recommend the clinical evaluation of WS extract in COVID-19 patients with a high propensity for lung inflammation.